1995
DOI: 10.1093/carcin/16.6.1311
|View full text |Cite
|
Sign up to set email alerts
|

Induction at high incidence of ductal prostate adenocarcinomas in NBL/Cr and Sprague-Dawley Hsd:SD rats treated with a combination of testosterone and estradiol-17β or diethylstilbestrol

Abstract: This study determined the incidence of prostate adenocarcinoma following long-term treatment of NBL and Sprague-Dawley rats with estradiol-17 beta or diethylstilbestrol (DES) plus testosterone and it defined the origin of these tumors. NBL and Sprague-Dawley rats were treated with two Silastic tubing implants (i.d. 1.6 mm, o.d. 3.2 mm) containing a 2 cm long filling of testosterone and one implant containing a 1 cm long filling of estradiol-17 beta or DES. Control animals received empty implants. Treated anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
161
2

Year Published

1997
1997
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(175 citation statements)
references
References 0 publications
12
161
2
Order By: Relevance
“…[2][3][4][5][6][7] These models support the hypothesis that changes in hormonal milieu are not only implicated in PRCA but may be causal. Although animal models of hormone-induced PRCA demonstrate a natural progression in vivo, they have a low penetrance, 8 long latency 4 and do not metastasize to distant organs.…”
mentioning
confidence: 56%
“…[2][3][4][5][6][7] These models support the hypothesis that changes in hormonal milieu are not only implicated in PRCA but may be causal. Although animal models of hormone-induced PRCA demonstrate a natural progression in vivo, they have a low penetrance, 8 long latency 4 and do not metastasize to distant organs.…”
mentioning
confidence: 56%
“…Alternatively, a subset of cells may be particularly susceptible to redox injury, whereas others may be totally resistant to development of carcinoma. In this context, previous studies 20,21 have suggested that carcinoma develops from periurethral ducts of the LP in the NBL rat model. It is important to note that we now also find evidence of OS/NS damage in these ducts.…”
Section: Discussionmentioning
confidence: 88%
“…19 Exposure of NBL rats to treatment with a combination of testosterone (T) and 17␤-estradiol (E2) for 16 weeks induces dysplasia accompanied by inflammation selectively in the lateral prostates (LPs), and longer exposure of these steroids induces a high incidence of adenocarcinomas in the LP. 20,21 However, neither of these lesions are induced in the ventral prostates (VPs) of all treated animals. 20 -24 Using the NBL experimental model, our current results provide evidence that this steroid treatment selectively causes major disruptive effects in the OS/NS of the LP that affects damage to DNA, protein, and lipids.…”
mentioning
confidence: 99%
“…The E capsules produce serum levels of ˜ 75 pg/ml in rats which, although elevated for males, is not considered pharmacologic (79). These T+E capsule for 16 weeks produce PIN in the dorsolateral prostates at 100% incidence in Noble rats (4) but only 33% incidence in Sprague-Dawley rats (80). At 28 weeks of age, the prostates were examined for hyperplasia, inflammation and PIN, the presumed precursor lesion of prostate cancer.…”
Section: Neonatal Exposure To Low-dose Estradiol and Bisphenol Amentioning
confidence: 99%